1995
DOI: 10.1177/10454411950060030301
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death and Cell Transformation in Craniofacial Development

Abstract: Fusion of branchial arch derivatives is an essential component in the development of craniofacial structures. Bilaterally symmetric branchial arch processes fuse in the midline to form the mandible, lips, and palate. The mechanism for fusion requires several different morphologic and molecular events prior to the completion of the mesenchymal continuity between opposing tissue processes. The ectodermal covering of the branchial arches is one of the cell types that has an important role during craniofacial deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 104 publications
(141 reference statements)
0
51
0
1
Order By: Relevance
“…One is the fate of MEE (Shuler, 1995) and the other is the requirement for TGF-␤3 (Kaartinen et al, 1995;Proetzel et al, 1995). Previous studies suggested that the specific effects of TGF-␤3 in MEE were controlled by T␤R-III modulating the access of TGF-␤ ligands to signaling receptors (Cui and Shuler, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One is the fate of MEE (Shuler, 1995) and the other is the requirement for TGF-␤3 (Kaartinen et al, 1995;Proetzel et al, 1995). Previous studies suggested that the specific effects of TGF-␤3 in MEE were controlled by T␤R-III modulating the access of TGF-␤ ligands to signaling receptors (Cui and Shuler, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The MEE from opposing sides contact in the midline and form an epithelial seam when the paired palatal shelves are approximated. As palatal fusion proceeds, the MEE seam quickly breaks down and ultimately the epithelial cells disappear from the midline (Shuler, 1995). It has been demonstrated that there are three distinct fates for MEE, which include epithelial-mesenchymal transformation (Shuler et al, 1991(Shuler et al, , 1992Griffith and Hay, 1992;Martinez-Á lvarez et al, 2000), migration (Carette and Ferguson, 1992), and programmed cell death (Mori et al, 1994;Martinez-Á lvarez et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…7). The palatal structures are composed of the CNC-derived ectomesenchyme and pharyngeal ectoderm (Ferguson, 1988;Shuler, 1995). The epithelia that cover the palatal shelves are regionally divided into oral, nasal, and medial edge epithelium (Fig.…”
Section: Palatogenesis and The Molecular Mechanism Of Cleft Palatementioning
confidence: 99%
“…The formation of the secondary palate in mammalian fetuses involves a series of developmental events that occur in a spatially and temporally coordinated manner (Ferguson, 1988;Hay, 1995;Shuler, 1995). Opposing bilateral palatal shelves elevate horizontally, grow medially and finally fuse with each other in the midline.…”
Section: Introductionmentioning
confidence: 99%